The Chlamydia trachomatis Protease CPAF Contains a Cryptic PDZ-Like Domain with Similarity to Human Cell Polarity and Tight Junction PDZ-Containing Proteins. - Kenneth R Maksimchuk; Katherine A Alser; Rui Mou; Raphael H Valdivia; Dewey G McCafferty (PLoS ONE, 2016)
The need for more effective anti-chlamydial therapeutics has sparked research efforts geared toward further understanding chlamydial pathogenesis mechanisms. Recent studies have implicated the secreted chlamydial serine protease, chlamydial protease-like activity factor (CPAF) as potentially important for chlamydial pathogenesis. By mechanisms that remain to be elucidated, CPAF is directed to a discrete group of substrates, which are subsequently cleaved or degraded. While inspecting the previously solved CPAF crystal structure, we discovered that CPAF contains a cryptic N-terminal PSD95 Dlg ZO-1 (PDZ) domain spanning residues 106-212 (CPAF106-212). This PDZ domain is unique in that it bears minimal sequence similarity to canonical PDZ-forming sequences and displays little sequence and structural similarity to known chlamydial PDZ domains. We show that the CPAF106-212 sequence is homologous to PDZ domains of human tight junction proteins.